Placing Education: The School as Architectural Space - Gislason, Neil (Paideusis, 2007)
School architecture is a vital part of the learning environment: An educational facility should actively support learning processes which are grounded on an applied, multidisciplinary curriculum. This paper argues, accordingly, that a school should provide flexible educative spaces which properly enable multiple forms of teaching and learning. Support for this thesis is drawn from spatial theory, John Dewey’s writing on educative spaces, architectural writing and ecological design theory. It is finally posited that we need move beyond certain industrial-era assumptions about learning, in order to lay the conceptual foundation for a dynamic notion of architecture for education.